Asthma Comorbidities: Frequency, Risk Factors, and Associated Burden in Children and Adolescents - Salvatore Fasola; Giuliana Ferrante; Giovanna Cilluffo; Velia Malizia; Pietro Alfano; Laura Montalbano; Giuseppina Cuttitta; Stefania La Grutta (MDPI AG, 2022)
Identifying asthma comorbidities in children is fundamental for improving disease management. We aimed to investigate the frequency of allergy-related comorbidities in children and adolescents with asthma, and to identify associated risk factors and disease burden. Between September 2015 and December 2018, 508 asthmatic patients (5-17 years) were consecutively enrolled. Parents answered a standardized questionnaire on the history of disease and risk factors. Comorbidities were classified based on the involvement of respiratory and/or extra-respiratory districts: asthma only (A, 13%), asthma with respiratory comorbidities (AR, 37%), asthma with extra-respiratory comorbidities (AER, 10%), and asthma with both respiratory and extra-respiratory comorbidities (ARER, 40%). Multinomial logistic regression showed that membership in the AR group was significantly associated with a maternal history of asthma (OR = 3.08, 95% CI: 1.23-7.72), breastfeeding ≥ three months (OR = 1.92, 1.06-3.46), early mold exposure (OR = 2.39, 1.12-5.11), and current environmental tobacco smoke exposure (OR = 2.06, 1.11-3.83). Membership in the AER group was significantly associated with the female gender (OR = 3.43, 1.54-7.68), breastfeeding ≥ three months (OR = 2.77, 1.23-6.22). ARER was significantly associated with all the aforementioned exposures. Patients with AR reported exacerbations in the last 12 months more frequently (p = 0.009). Several personal and environmental risk factors are associated with comorbidities in asthmatic children and adolescents, possibly worsening the disease burden.